(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article offers a comprehensive examination of stylistics, focusing on the phono-graphical and morphological levels of language analysis. It addresses the significance of sounds and written symbols in the stylistic composition of literary texts, outlining the impact of phonetics, phonology, and graphology. The article also explores the intricate ways in which words are formed and structured, delving into the morphological aspects of language that affect textual style. Special attention is given to how these linguistic features influence the reader’s interpretation and contribute to the thematic depth and emotional resonance of literature. Through detailed examples, the article demonstrates the practical application of these concepts in the analysis of poetry and prose, ultimately enhancing the reader’s appreciation of the literary art form.